«La mujer por fuerza», «El condenado por desconfiado» and «El burlador de Sevilla», Three Comedies Attributed to Tirso de Molina (Castilla. Estudios de Literatura, 2022)
We expose three attribution problems in several cases of doubtful authorship in the theater of the Siglo de Oro: El condenado por desconfiado and La mujer por fuerza, both edited as Tirso’s works in the problematic Segunda parte and El burlador de Sevilla, edited under the name of Tirso in the volume Doze comedias de Lope de Vega y otros autores (about 1630). We have applied a methodology concerning the analysis of metaphors and inusual lexical items, and we have comparated it with several works by the two dramaturgians concerned by its attributions, Tirso and Claramonte, and also with several others, as reference group. We conclude that La mujer por fuerza is a work by Tirso, El burlador de Sevilla is a Claramonte’s work, and El condenado por desconfiado is also a work by Claramonte, perhaps with a collaboration from Mira de Amescua.